Schistosomiasis control in China: the impact of a 10-year World Bank Loan Project (1992-2001) - Xianyi Chen; Liying Wang; Jiming Cai; Xiaonong Zhou; Jiang Zheng; Jiagang Guo; Xiaohua Wu; Engels D.; Minggang Chen (The World Health Organization, 2005)
China has been carrying out large-scale schistosomiasis control since the mid-1950s, but in the early 1990s, schistosomiasis was still endemic in eight provinces. A World Bank Loan Project enabled further significant progress to be made during the period 1992-2001. The control strategy was focused on the large-scale use of chemotherapy - primarily to reinforce morbidity control - while at the same time acting on transmission with the ultimate goal of interrupting it. Chemotherapy was complemented by health education, chemical control of snails and environmental modification where appropriate. A final evaluation in 2002 showed that infection rates in humans and livestock had decreased by 55% and 50%, respectively. The number of acute infections and of individuals with advanced disease had also significantly decreased. Although snail infection rates continued to fluctuate at a low level, the densities of infected snails had decreased by more than 75% in all endemic areas. The original objectives of the China World Bank Loan Project for schistosomiasis control had all been met. One province, Zhejiang, had already fulfilled the criteria for elimination of schistosomiasis by 1995. The project was therefore a success and has provided China with a sound basis for further control.